2022
DOI: 10.1039/d1tc03142b
|View full text |Cite
|
Sign up to set email alerts
|

Doping of graphene via adlayer formation of electrochemically reduced dibenzyl viologen

Abstract: Doping of graphene by self-assembled molecular network of uncharged dibenzyl viologen (DBV0) generated in situ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…This report provided direct evidence of a change in the work function of viologen-doped graphene . Recently, we demonstrated that the doping degree of CVD graphene on SiO 2 is modulated by the uncharged DBV 0 molecules, electrochemically generated . In addition, the neutral form of DBV was successfully used to modulate the charge transfer and band gap of MoS 2 and bilayer graphene, respectively …”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…This report provided direct evidence of a change in the work function of viologen-doped graphene . Recently, we demonstrated that the doping degree of CVD graphene on SiO 2 is modulated by the uncharged DBV 0 molecules, electrochemically generated . In addition, the neutral form of DBV was successfully used to modulate the charge transfer and band gap of MoS 2 and bilayer graphene, respectively …”
Section: Introductionmentioning
confidence: 78%
“…(a) CVs of HOPG and G-Cu in 50 mM HCl (black and gray curves) and in 0.1 mM DBV 2+ + 50 mM HCl (red and blue curves). The colored bars illustrate the regimes where a particular DBV-species is the dominant one: green: DBV 2+ , orange: DBV •+ , purple: DBV 0 , and pink: transient regime; (b) the redox processes of DBV show the transformation between dicationic, monocationic, and uncharged molecules upon capturing/releasing electrons (reproduced from ref with permission from the Royal Society of Chemistry).…”
Section: Resultsmentioning
confidence: 99%
“…Non-covalent functionalization of electrode surfaces has been employed for designing these types of heterogeneous catalysts [4,29,[32][33][34]. Compared with other approaches, this approach dealing with two-dimensional (2D) materials including carbon-basedas well as transition metal dichalcogenides(TMDs)materials has been intensively focused on due to theintrinsic properties of the latter materials, including distinct thickness-dependent optoelectronic properties, large surface areas, and enormous experimental charge mobilities that facilitate the electrocatalytic activities [35][36][37][38][39]. In particular, a molecular approach to investigate the electrocatalytic HER process of a twodimensional system consisting of catalytically active porphyrin molecules and atomically thin graphene electrodes was also conducted in order to verify the HER mechanism at the molecular scale [40].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 So far, two parallel approaches have been applied to modify the graphene surface: physisorption and chemisorption. [11][12][13][14][15][16][17][18] For physisorption, organic molecules randomly adsorb or selfassemble onto the graphene surface via weak intermolecular interactions, thereby preserving the intrinsic properties of graphene. However, these systems are usually not robust, which may limit stability against temperature and other environmental changes.…”
Section: Introductionmentioning
confidence: 99%